2017
DOI: 10.1038/ajg.2016.531
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind, Placebo-Controlled Trial to Examine the Effectiveness of Lubiprostone on Constipation Symptoms and Colon Transit Time in Diabetic Patients

Abstract: This study suggests that lubiprostone is a safe and effective treatment for increasing weekly SBMs and decreasing CTT in patients with DM and CIC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 24 publications
0
32
0
2
Order By: Relevance
“…There were no safety concerns. There is, however, a lack of safety data of lubiprostone in PD patients, but because of the data available in the general and geriatric population, lubiprostone is considered to pose an “ acceptable risk without specialized monitoring .” Typical AEs of lubiprostone include nausea, diarrhea, and dyspnea …”
Section: Results and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no safety concerns. There is, however, a lack of safety data of lubiprostone in PD patients, but because of the data available in the general and geriatric population, lubiprostone is considered to pose an “ acceptable risk without specialized monitoring .” Typical AEs of lubiprostone include nausea, diarrhea, and dyspnea …”
Section: Results and Conclusionmentioning
confidence: 99%
“…Typical AEs of lubiprostone include nausea, diarrhea, and dyspnea. 106,107 Probiotics and prebiotic fiber were evaluated in 1 high-quality, positive study. 40 The new conclusions are "efficacious" and "clinically useful."…”
Section: T R E a T M E N T O F T H E N O N M O T O R S Y M P T O M S mentioning
confidence: 99%
“…Both agents have been shown to stimulate intestinal fluid secretion and transit. Lubiprostone, a peripheral-acting derivative from prostaglandin E1 that activates CIC-2 chloride channels stimulating intraluminal fluid secretion, has been studied in a diabetic population [29••]. …”
Section: Treatment Considerations In Constipation (Table 1)mentioning
confidence: 99%
“…A recent randomized, double-blind controlled trial examined the effectiveness of lubiprostone on constipation symptoms and colonic transit time specifically in diabetics [29••]. In this trial, 76 diabetic patients were randomized with baseline measurements of spontaneous bowel movements (SBM), quality of life, and colon transit time (utilizing a wireless motility capsule).…”
Section: Treatment Considerations In Constipation (Table 1)mentioning
confidence: 99%
“…This study does not address whether lubiprostone is effective and well tolerated in medically complex patients as the study design excluded patients with any significant co-morbid medical conditions, specifically in the diabetic population. The effect of lubiprostone in such populations was recently reported in a study by Christie et al [13] that addressed lubiprostone use in a diabetic population with CIC. The authors reported that lubiprostone improved complete spontaneous bowel movement (CSBM) without increasing nausea compared to placebo as assessed using wireless motility capsule and colon transit time, coupled with quality-of-life questionnaires.…”
mentioning
confidence: 81%